2017
DOI: 10.20448/journal.505.2017.41.1.8
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Poor Female Understanding about Health Hazards of Indoor Air Pollution in Bangladesh

Abstract: This paper will identify health hazards associated with indoor air pollution (IAP) in Bangladesh. Research into IAP in Bangladesh has been neglected for many decades. This neglect may reflect aspect of the marginalization of women in Bangladeshi society, especially as cooking is considered a social responsibility of women. The main purposes of the paper are to examine types of the IAPrelated health threats female domestic cook experienced and to understand their level of awareness about the link between IAP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Women and children are relatively more expose to indoor air-pollution induced diseases. Therefore, (Banik, 2010) investigate the impact of indoor air pollution on female health in Bangladesh by conducting interviews of one hundred women are interviewed by using a semi-structured questionnaire. The study found a significant positive impact of indoor pollution exposure to female health.…”
Section: Gender and Public Healthmentioning
confidence: 99%
“…Women and children are relatively more expose to indoor air-pollution induced diseases. Therefore, (Banik, 2010) investigate the impact of indoor air pollution on female health in Bangladesh by conducting interviews of one hundred women are interviewed by using a semi-structured questionnaire. The study found a significant positive impact of indoor pollution exposure to female health.…”
Section: Gender and Public Healthmentioning
confidence: 99%
“…Women and children are the most susceptible to this hazard. Women spend the most time indoors in close proximity to the stove (Banik 2017). Women and children are also vulnerable to injury and violence when out collecting fuel, and the time-consuming activity of gathering fuel detracts from other productive activities and keeps children away from school (WHO 2014).…”
Section: Household Air Qualitymentioning
confidence: 99%
“…With subsidies and government intervention through policy, the use of clean fuels could be proliferated and the (Miah et al 2009;Banik 2017;Junaid et al 2018). Urmee and Gyamfi (2014) reasoned that subsidies should also be provided for training local ICS designers and manufacturers who can pass on knowledge to the users, rather than to just subsidize the cost for poor families, making the initiative more sustainable, as many ICS programs have collapsed with the end of donor funding.…”
Section: Institutionsmentioning
confidence: 99%
See 1 more Smart Citation